Characterization of nerve growth factor‐induced mechanical and thermal hypersensitivity in rats. (23rd August 2012) - Mills, C.D.; Nguyen, T.; Tanga, F.Y.; Zhong, C.; Gauvin, D.M.; Mikusa, J.; Gomez, E.J.; Salyers, A.K.; Bannon, A.W.
Abstract Background Injection of nerve growth factor (NGF) produces mechanical and thermal hypersensitivity in rodents and humans. Treatment with sequestering antibodies demonstrates the importance of NGF in various pain states, with efficacy seen in a number of animal pain models and in painful human conditions. However, these phenomena have not been evaluated in the context of using NGF‐induced hypersensitivities as a model of pain. Methods NGF‐induced behaviours were characterized using von Frey filament, pinprick and thermal endpoints and then pharmacologically evaluated with known reference agents. Results Intraplantar NGF injection produced a dose‐dependent increase in thermal sensitivity that lasted through 24 h post‐injection and an immediate long‐lasting (2 week) increase in mechanical sensitivity at the injection site, with no effects detected at secondary sites. NGF‐induced mechanical sensitivity was pharmacologically characterized at 4 h and 1 week post‐NGF injection. The nonsteroidal anti‐inflammatory drugs (NSAIDs), celecoxib and diclofenac, were minimally effective against both thermal and mechanical endpoints. Gabapenitn and duloxetine were only moderately effective against thermal and mechanical hypersensitivity. Morphine was effective against thermal and mechanical endpoints at every time point examined. Treatment with the transient receptor potential vanilloid 1 (TRPV1) antagonist A‐784168 partially attenuated NGF‐induced thermal and mechanical sensitivity at all time points examined. Conclusions The results reported here suggest that effects of NGF on thermal and mechanical sensitivity in rats are similar to those reported in human and are partially driven by TRPV1. The rat NGF model may serve as a potential translational model for exploring the effects of novel analgesic agents.